Analisis Nilai Moral dalam Novel Lelaki Laut Karya Alamsyah M. Djafar serta Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Aam Nurjaman; Utami Kusumawati Fuad (Triangulasi: Jurnal Pendidikan Kebahasaan, Kesastraan, Dan Pembelajaran, 2021)
The purpose of this research is to find out the moral value of Lelaki Lautâ€ novel written by Alamsyah M. Djafar and the suitable of this novel as the teaching material of Bahasa Indonesia lesson in senior high school. Qualitative method is used in this research. Library research is used as the technique  the Lelaki Lautâ€ novel written by Alamsyah M. Djafar is the resource of this research. The moral value from this novel is the relationship between human and themselves, the relationship between human and another human in the social area includes their nature, and the relationship between human and God. There are found 47 moral values after analysing the quotation. Those 47 results are included the types of teh moral value. The most data found are 21 (45%) about the relationship between human and themselves. This relationship usually about their own feelings and they appear naturally. The second data which are found the most are 18 (38%) about the relationship beetween human and another human in their social area includes their relationship with the nature. These moral value show that and issue comes from the human interaction and the influence of their environment. Next, the human relation with their God is found total 8 (17%)  data. This moral value is related to the problem of their loyalty and trust to their God. Based on these total, it can be concluded that Lelaki Lautâ€ novel written by Alamsyah M. Djafar has alot of moral values besides, it can be concluded also that this Lelaki Lautâ€ novel has implication on the Bahasa Indonesia lesson in senior high school. The Lelaki Lautâ€ novel also is suitable to be used as the teaching material in Bahasa Indonesia  lesson in senior high school. These things can be seen from the amount of the moral values from Lelaki Lautâ€ novel.